Women’s Stories in the Quran as Models of Social Agency and Gender Justice - Yaghoob Mokhtarzadeh; Sina Ghadimi Malladi; Hanan Archi Zaenah; Kaveh Börner; Seid Anne Sharan (Arba: Jurnal Studi Keislaman, 2026)
The stories of women in the Quran are often interpreted through a patriarchal framework that positions women as didactic objects. At the same time, the dimension of their social agency has received less systematic attention in exegetical studies. Although gender discourse in Islamic studies is developing rapidly, there is little research that thematically and narratively examines how the structure of the Quranic story itself represents women as autonomous subjects while also articulating the principle of gender justice inherently. This study specifically analyses the representation of social agency in the stories of Mary, the mother of Moses; the Queen of Sheba; and the wife of Pharaoh, and identifies their relationship to the construction of gender justice in the Quranic narrative. This study uses a qualitative approach, employing thematic interpretation of related verses, followed by narrative-contextual analysis to map patterns of decision-making, configurations of power relations, and articulations of moral responsibility, and engaging in critical dialogue with selected classical and contemporary commentaries based on their influence and representativeness. The results of the study show three main findings: first, the Quranic narrative consistently presents women as moral agents who make strategic decisions in crises; second, the stories demonstrate women’s social interventions in domestic and public spaces that have had historical impact; third, their narrative structures affirm the equality of ethical responsibility and rational capacity between men and women. These findings confirm that gender agency and justice are intrinsic dimensions of Quranic narratives and have implications for reconstructing an interpretive methodology that is more responsive to a gender justice perspective.